Last Man in Tower - Adiga, Aravind (Gurugram: Fourth Estate, 2011)
A tale of one man refusing to leave his home in the face of property development. Tower A is a relic from a co-operative housing society established in the 1950s. When a property developer offers to buy out the residents for eye-watering sums, the principled yet arrogant teacher is the only one to refuse the offer, determined not to surrender his sentimental attachment to his home and his right to live in it, in the name of greed. His neighbours gradually relinquish any similar qualms they might have and, in a typically blunt satirical premise take matters into their own hands, determined to seize their slice of the new Mumbai as it transforms from stinky slum to silvery skyscrapers at dizzying, almost gravity-defying speed.
Keywords: Real estate development -- Fiction -- Apartment houses -- Community life -- India$1 (BMumbais